Intracardiac fungal mass in extreme premature patient - Diaz Rojas, Milagros C. (2022)
There are few reports on intracardiac fungal masses, especially in the pediatric population. We present the case of an extremely premature patient who, after being hospitalized since birth in an intensive care unit, developed fungal masses in the right atrium, which, due to their size, location and resistance to medical treatment, required surgical excision. For this reason, at the slightest suspicion of systemic candidiasis in pediatric patients, it is mandatory to include an echocardiogram in the defocalization examinations to rule out endocarditis and thus avoid the development of intracardiac fungal masses. Therefore, early detection for timely medical management may avoid the surgical approach associated with a high risk of morbidity and mortality in extremely premature patients.